From Temporary Migrants to Permanent Attractions : Tourism, Cultural Heritage, and Afro-Antillean Identities in Panama - Guerrón-Montero, Carla María, 1970- (Book collections on Project MUSE., 2020)
"A new reading of Panama's nation-building process, interpreted through a lens of transnational tourism"--